Perkembangan Budaya Berpakaian Mahasiswi Universiti Malaya: Isu dan Cabaran: Cultural Development of Universiti Malaya’s Students Dressing: Issues and Challenges - Abdul Manaf, Noor Zulaikha Azlin; Ali @ Mat Zin, Aizan (Journal Al-Muqaddimah, 2024)
This article aims to examine the evolution of the dressed culture of Malaya University students along with its issues and challenges. Along with the current of modernization, the traditional clothing culture has changed and developed with the change of times. A string of such developments, there are issues and challenges faced by students in the choice of clothes while being on campus in particular. The question is, are the factors driving the change in the development as well as the issues and challenges that arise as a result of the development of the use culture among female students at the University of Malaya. The collection of research data has used methods of documentation, observation and questions in exploring primary and secondary materials related to the objectives of the study. The data collected has been analyzed scientifically, inductive, deductive and comparative to produce findings of the research. The results of the study found that students choose clothes based on the influence of schoolmates overcoming the Islamic dress guidelines. In conclusion, clothing trends will continue to evolve over time and era. But it needs to be in line with sharia guidelines.